Retraction: Preparation and properties of polymer micelle-embedded nanofibrous membranes for dual-drug co-delivery and multistep release. Issue 86 (31st August 2016) - Zhao, Hui; Wei, Zhen; Xu, Shuxin; Tang, Minjie; Deng, Liandong; Zhang, Jianhua; Dong, Anjie
Abstract : Retraction of 'Preparation and properties of polymer micelle-embedded nanofibrous membranes for dual-drug co-delivery and multistep release' by Hui Zhao et al., RSC Adv., 2015, DOI: 10.1039/c5ra03345d.